The Relationship of Grit Traits on Stress Level and Academic Achievement Among University Malaysia Sabah (UMS) Students - Nur Sabrina Suhaimie; Norafifah Bali; Razima Hanim Osman; Wanda Kiyah Anak George; Murnizam Halik; Mohd Sobri Ismail (Penerbit UMS, 2021)
Traditionally, academic achievement and success is often measured by cognitive abilities such as aptitude and intelligence. However, the grit concept has received attention from researchers as the predictor for academic achievement. Dimensions of grit which are Perseverance of Effort (PE) and Consistency of Interest (CI) plays a different role in an individual. Hence, this quantitative study is conducted to examine the relationship of grit traits on academic achievement and stress level among University Malaysia Sabah (UMS) students. In addition, it also examines the differences of dimensions of grit between gender and differences of grit on students’ academic achievement. The study sample consisted of 220 UMS students and was conducted using two instruments, 12- item Grit Scale (Grit-O) and Depression, Anxiety, Stress Scale (DASS-21). Result findings showed no significant relationship of dimensions of grit on academic achievement. Whereas, there is a variety of finding for the relationship of dimensions of grit on stress level. However, only CI is influenced by stress level, while PE does not have any influence. The differences towards dimensions of grit and gender and grit on students’ academic achievement also showed no significant difference which explains that students based on gender and academic achievement categories have the same level of grit. Hence, the overall findings of this study contribute to the increased understanding of the complexities related to the relationship of grit on academic achievement and stress level. Additional limitations and implications are presented along with offerings for further research recommendations.